ANALYSIS OF THE SELECTION OF TOURIST BUS TERMINAL LOCATIONS IN YOGYAKARTA CITY - Bieffe Annelis Ashita; Dwijoko Ansusanto (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2025)
The growth of tourism in Yogyakarta City has led to an increase in the need for tourist terminal facilities that are able to regulate the movement of tourist buses in a more orderly, efficient, and safe manner, especially in the strategic area of Gumaton (Tugu-Malioboro-Kraton) which has the highest rate of visits in the city. This research aims to determine the most ideal location for the development of tourist terminals through spatial analysis approaches, field surveys, SWOT analysis, and Analytic Hierarchy Process (AHP) methods. Primary data was obtained through surveys of bus movements at five main intersections, physical observation of road sections, and distribution of questionnaires to tourists, bus drivers, the community, business actors, and government stakeholders. Meanwhile, secondary data was obtained from the Yogyakarta City RTRW, tourist visit statistics, and transportation regulations. The AHP assessment criteria include accessibility, RTRW suitability, transportation network integration, land availability and technical feasibility, traffic and safety impact, and environmental sustainability. The AHP results showed that the Giwangan Terminal obtained the highest score of 59.75%, followed by the Ngabean crime scene at 27.28%, Jalan Margo Utomo at 7.20%, and Jalan Jenderal Sudirman at 5.78%, with a Consistency Ratio (CR) value of 0.033 which indicates the consistency of a valid matrix. This finding is strengthened by SWOT results which show that Giwangan has significant advantages in terms of land availability, accessibility, and spatial suitability. Thus, Giwangan Terminal is designated as the most feasible location for the development of Yogyakarta City tourist terminals in the short and long term.